2014
DOI: 10.5530/pj.2014.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tribulus Terrestris on Learning and Memory in Wistar Rats

Abstract: Objectives: The present study was designed to evaluate the effect of aqueous extract of fruits of Tribulus terrestris on learning and memory in rodents. Materials and Methods: Thirty wistar rats were divided in 5 groups of 6 rats each. Baseline values for the time taken to reach reward chamber (TRC) in the Hebb William Maze and transfer latency (TL) in the T-maze were recorded on Day 1. Mean of 5 sessions was calculated for each rat. Group I was normal control, group II piracetam standard, group III, IV and V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The effect of the water extract of TT fruits on learning and memory ability in rodents was evaluated by recording the time of reaching the reward chamber (TRC) in the Hebb William Maze and the transfer latency (TL) in the T-zema. The results showed that the water extract of TT fruits significantly reduced the time of arrival at the maze in a dose-dependent manner [ 108 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The effect of the water extract of TT fruits on learning and memory ability in rodents was evaluated by recording the time of reaching the reward chamber (TRC) in the Hebb William Maze and the transfer latency (TL) in the T-zema. The results showed that the water extract of TT fruits significantly reduced the time of arrival at the maze in a dose-dependent manner [ 108 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…TT extracts have therapeutical potential for the recovery of normal skin barriers. 227 Ghareeb et al 228 examined extracts of Calluna vulgaris, Ferula hermonis, and TT and found that the activity depended on the concentration of antiacetylcholinesterase. The 3 extracts showed antioxidant function as they inhibited 1,1-diphenyl-2-picryl hydrazyl oxidation and production of thiobarbituric acid reactive substances.…”
Section: Other Pharmacological Uses Of T Terrestrismentioning
confidence: 99%
“…El-Tantawy and Hassanin 212 found that TT saponins revitalized β-cells of pancreatic islets. Nam et al 227 reported the modulatory effect of TT fruits on atopic dermatitis through modulating the activities of calcium ion channels, Orai1 and TRPV3. TT extracts have therapeutical potential for the recovery of normal skin barriers.…”
Section: Other Pharmacological Uses Of T Terrestrismentioning
confidence: 99%
“…Fructus Tribuli (FT), which is the dried fruit of Tribulus terrestris L. [ 7 ], is renowned in TCM as Ji-Li and has been used for thousands of years in Asian countries. Several previous investigations focused on its pharmacological activities demonstrated that FT improved sexual function [ 8 ], could be used to prevent and treat cardiovascular diseases [ 9 ], had neuroprotective [ 10 ] and memory improvement activity [ 11 ], and provided antidiabetic [ 12 ], antidepression [ 13 ], anti-inflammatory [ 14 ], and antioxidant effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%